Lymphocyte Count and Body Mass Index as Biomarkers of Early Treatment Response in a Multiple Sclerosis Dimethyl Fumarate-Treated Cohort - Manni, Alessia; Iaffaldano, Antonio; Lucisano, Giuseppe; D'Onghia, Mariangela; Mezzapesa, Domenico Maria; Felica, Vincenzo; Iaffaldano, Pietro; Trojano, Maria; Paolicelli, Damiano (Frontiers in Immunology, 2019)
Introduction: In relapsing Multiple Sclerosis (RMS) patients treated with disease modifying drugs (DMDs), few data are available regarding the biomarkers of treatment response. We aimed to assess the predictive value of lymphocyte count (LC) and Body Mass Index (BMI) for treatment response in a real life setting of dimethyl fumarate (DMF) treated patients. Materials and Methods: We included in our observational analysis 338 patients who were prescribed DMF in an Italian MS Centre. We collected clinical and demographic data at the beginning of DMF (T0), and assessed White Blood Cells (WBC) and LC at T0 and at 3 (T3), 6 (T6), 9 (T9) and 12 (T12) months. Gadolinium enhancing (Gd+), new T2 lesions and relapses within the first year of treatment (T12) were recorded in order to evaluate clinical activity at 12 months. Analysis of correlation was performed to correlate WBC, LC and BMI with clinical and radiological responses. We evaluated whether BMI or LC can predict treatment response by using multivariate logistic regression models at each follow-up. Results: Our cohort was followed up for a mean period of 19.8 ± 6.8 months. The mean BMI at baseline was 24.19±4.48. The multivariate models gave as predictive factors for Gd+ lesions at T12, LC at T3 (OR=1.003, 95% CI= 1.00-1.07; p=0.046) and baseline BMI (OR=0.71, 95% CI= 0.52-0.98; p=0.037). Predictive factors for new T2 lesions at T12 were LC at T3 (OR=1.01 95%CI=1.00-1.95; p=0.005) and baseline BMI (OR=0.99, 95% CI=0.98-1.00; p=0.026). Conclusions: In our real life-experience, BMI and LC may be early biomarkers to predict treatment response during DMF.